Task failure during high-intensity exercise is associated with a critical reduction in tissue oxygenation - Bishop, D.; Bortolotti, S.; Ferri, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Task failure is an important feature of performance, ageing and many diseases. Three popular models suggest that task failure may be due to: a) a failure of skeletal muscle motor unit recruitment (1); b) depletion of a fixed, critical, muscle energy store (2); or c) a critical reduction in tissue oxygenation (3). The purpose of this study was to assess the hypothesis that task failure during high-intensity, whole-body exercise may be associated with a critical reduction in tissue oxygenation. Methods Six well-trained cyclists (VO2max: 67.6 +/- 6.3 mL/kg/min) performed an incremental test to exhaustion on a cycle ergometer. They then performed a familiarisation session, followed by, in a random order, constant-load exercise tests at 100, 110 and 120% of VO2max until task failure. During these trials, near-infrared spectroscopy (NIRS) was used to monitor changes in the concentration (µM) of oxygenated haemoglobin (Hb) and myoglobin (Mb) (delta[02Hb]), deoxygenated Hb+Mb (delta [HHb]) in the right vastus lateralis muscle and the frontal cerebral cortex. Oxygen uptake (VO2) and rating of perceived exertion (RPE) were also monitored during all 3 trials. The study had ethics approval and all subjects signed a statement of informed consent prior to the study. Results At task failure, there was no significant difference between the three conditions for delta[HHb] (40 +/- 5 vs 39 +/- 8 vs 37 +/- 7 µM; P>0.05), delta[02Hb] (23 +/- 5 vs 26 +/- 6 vs 22 +/- 3 µM; P>0.05), VO2 (67.6 +/- 4.5 vs 67.4 +/- 3.8 vs 64.7 +/- 4.1 mL/kg/min) or RPE (20 vs 20 vs 20; P>0.05). There were also no significant differences between trials for cerebral oxygenation levels. Discussion Our delta[02Hb] and delta[HHb] values, for both the right vastus lateralis muscle and the frontal cerebral cortex, are similar to those previously reported in the literature (3). We report for the first time however, that task failure during 3 different exercise intensities occurred at similar tissue oxygen (and oxygen consumption) levels. While further research is required, our results raise the possibility that task failure during high-intensity exercise (at sea level) may be associated with an inability to further increase the rate of aerobic energy supply. References 1. Davis, J. M. and S. P. Bailey. Med Sci Sports Exerc. 29:45-57, 1997. 2. Monod, H. and J. Scherrer. Ergonomics. 8:329-338, 1965. 3. Subudhi, A. W., A. C. Dimmen, and R. C. Roach. J Appl Physiol. 103:177-183, 2007.